Genetic variation and phylogeographic structure of Spodoptera exigua in western China based on mitochondrial DNA and microsatellite markers - Wang, Xing-Ya; Wang, Ming-Ming; Chen, Chen; Wang, Xiao-Qi (PloS one, 2020)
The beet armyworm, Spodoptera exigua, is a significant agricultural pest of numerous crops and has caused serious economic losses in China. To effectively control this pest, we analyzed its genetic variation, population genetic structure and demographic history. We used mitochondrial DNA (mtDNA) fragments of the cytochrome oxidase subunit I (COI) and eight nuclear microsatellite loci to investigate genetic diversity and population genetic structure of S. exigua populations at 14 sampling sites in western China. Both mtDNA and microsatellite data indicated low levels of genetic diversity among all populations. A moderate genetic differentiation among some S. exigua populations was detected. Neighbor-joining dendrograms, STRUCTURE, and principal coordinate analysis (PCoA) revealed two genetically distinct groups: the KEL group and the remaining population group. Isolation by distance (IBD) results showed a weak significant correlation between geographic distance and genetic differentiation. Haplotype networks, neutrality testing, and mismatch distribution analysis indicated that the beet armyworm experienced a recent rapid expansion without a recent genetic bottleneck in western China. Thus, the results of this population genetic study can help with the development of strategies for managing this highly migratory pest.